A Factor Analysis of Drug Cased Prisoners’ Buddhist Intellectual Well-Being - Linphoo, Montree; Phrayai, Narumol; Prasertsin , Ujsara; Jinngee, Prateep (Dhammathas Academic Journal, 2022)
The purposes of this research were 1) to study the dimension of the drug cased prisoners’ Buddhist intellectual well-being and 2) to investigate the congruence between the structured model of the drug cased prisoners’ Buddhist intellectual well-being and the empirical data. This study of factor Analysis of prisoners’ Buddhist intellectual well-being was quantitative research. The group of samples was 200 drug cased prisoners as dealer, addict and both who were sentenced to prison between one year up to ten years within the jail of Nakon Sawan Province in 2020, selected by criterion purposive sampling. The tool was the prisoner Buddhist intellectual well-being scale, total of 33 items. The reliability was at 0.76 and the statistic usedin data analysis was the Confirmatory Factor Analysis (CFA). The research findings were as follows: 1. Confirmatory Factor Analysis of prisoners’ Buddhist intellectual well-being consisting of three factors were (1) knowing (2) awakening, and (3) delighting. 2. The model of the drug cased prisoners’ Buddhist intellectual well-being structure was fit to the empirical data with Chi-square (X2) = 2.29 (p-value = 0.51), GFI = 0.99, AGFI = 0.98, RMSEA = 0.00, SRMR = 0.04, standardized factor loading between 0.56-0.71, and all elements were statistically significant at 0.05 level.